Kepribadian Konselor Perspektif Saiful Akhyar Lubis - Nurul Asyikin; Nurussakianah Daulay; Muhammad Riduan Harahap (Dinasti Review, 2024)
This research aims to 1) To analyze the personality of healthy counselors and the personality of unhealthy counselors from the perspective of Saiful Akhyar Lubis. 2) To analyze the role of the personality of unhealthy healthy counselors perspective Saiful Akhyar Lubis. 3) To analyze the factors that influence the emergence of an unhealthy healthy counselor personality from the perspective of Saiful Akhyar Lubis. 4) To analyze the relevance of Saiful Akhyar Lubis's thoughts on the counselor's personality to Islamic Education.The type of research used in this study is qualitative. The research design uses a character study approach. The data sources used are written sources by collecting the works of figures and related previous studies. The results of the research are 1) According to Saiful Akhyar Lubis, a healthy counselor has a personality of 10 criteria with the designation as a mentor. Conversely, unhealthy counselors have bad temper, weak faith, unstable emotions, lack of empathy, low intelligence, lack of integrity and unhealthy mentality. 2) According to Saiful Akhyar Lubis, the counselor's personality role is with five roles, namely as a guidance assistance service, manager, consultant, work team, and source of service information to counselees. 3) According to Saiful Akhyar Lubis, the factors that influence the emergence of healthy and unhealthy counselor personalities are two factors, namely internal and external. 4) The relevance of Saiful Akhyar Lubis' thoughts on personality in Islamic Education is divided into two, namely educators as counselors and counselors as educators.